Optimization Of Physical Conditions For The Production Of L-Glutamic Acid By A Mutant Micrococcus Glutamicus AB100. - S. GANGULY,; A. K. BANIK, (International Journal of Pharma and Bio Sciences, 2011)
Experimental studies were carried out to improve L-glutamic acid production using a biotin requiring auxotrophic mutant Micrococcus glutamicus AB100 by optimizing different physical parameters namely initial pH, period of incubation, volume of medium, age of inoculum, volume of inoculum and temperature. Maximum production of L-glutamic acid was obtained with initial pH, 6.5; period of incubation, 72h; volume of medium, 20ml; age of inoculum, 48h; volume of inoculum, 4% and temperature, 29oC. Production was increased significantly (p < 0.01) from 6.8 to 10.4 mg/ml. Dry cell weight changed significantly (p < 0.01) from 2.3 to 4.6 mg/ml.